Preparation of Three‐Dimensional Copper‐Zinc Alloy Current Collector by Powder Metallurgy for Lithium Metal Battery Anode. Issue 13 (1st July 2021) - Qiang, Zhe; Liu, Bao; Yang, Bingjun; Ma, Pengjun; Yan, Xingbin; Wang, Bixia
Abstract: Lithium metal batteries (LMB) have been considered as the most promising energy storage devices for electric vehicles and portable electronic devices, however their applications are usually limited due to the poor cycle stability and serious safety problems of the battery, which were caused by uncontrolled growth of lithium dendrite and unlimited volume change of anode during Li plating/stripping. Herein, we design a three‐dimensional porous copper‐zinc alloy (3D Cu−Zn) by powder metallurgy method, which has suitable and controllable porous structure for lithium deposition in lithium metal battery. By systematically tailoring particle size of metal powder and other parameters, the 3D Cu−Zn was prepared, which can be used as current collector of lithium anode and shows good cyclic stability. The Li metal anode with 3D Cu−Zn porous current collector can stably cycle for as long as 800 h under a high Li plating/stripping capacity of 1 mA h cm −2 and high current density of 1 mA cm −2 . Li@3D Cu−Zn||LiFePO4 cell has excellent rate performance and cycle performance. This work may open a new avenue for building better lithium metal battery with long cycle performance. Abstract : A three‐dimensional porous copper‐zinc alloy (3D Cu−Zn) is assembled by powder metallurgy method. The Li metal anode with 3D Cu−Zn porous current collector can stably cycle for as long as 800 h under a high Li plating/stripping capacity of 1 mA h cm −2 and a high current density of 1 mA cm −2 . Li@3D Cu−Zn||LiFePO4 cell has excellent rate performance and cycle performance.